Mesoporous polydopamine nano composite material, molecularly imprinted electrochemical sensor as well as preparation method and application of molecularly imprinted electrochemical sensor

By using mesoporous polydopamine nanocomposites and electrochemical polymerization in electrochemical sensors, the problems of low selectivity and environmental pollution in the existing technology of Mid-colchicine detection are solved, and high sensitivity and specificity analysis are achieved , has good reproducibility and reusability.

CN119307000APending Publication Date: 2025-01-14HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411559179.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing electrochemical sensors have problems such as low selectivity, insufficient sensitivity, and environmental pollution during the preparation process when detecting colchicine, and are subject to mass transfer and poor electrical signal response.

Method used

Mesoporous polydopamine nanocomposites are used as substrates to form a molecular imprint layer by electrochemical polymerization, and the signal response is improved by loaded gold nanoparticles, and a high-performance molecular imprint electrochemical sensor is constructed through electrochemical polymerization and blotting technology.

Benefits of technology

Sensitive and specific analysis of colchicine is achieved, with a linear range of as wide as 5 to 200 μmol/L, a detection limit as low as 2 μmol/L, and a sensor has good reproducibility and reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307000A_ABST
    Figure CN119307000A_ABST
Patent Text Reader

Abstract

The invention discloses a mesoporous polydopamine nano composite material, a molecular imprinting electrochemical sensor and a preparation method and application thereof. The preparation method comprises the following steps: polishing the surface of a glassy carbon electrode; adding the mesoporous polydopamine nanocomposite material loaded with gold nanoparticles into water to prepare a dispersion liquid, dropwise adding the dispersion liquid to the surface of the glassy carbon electrode, and drying to obtain the glassy carbon electrode coated with the mesoporous polydopamine nanocomposite material on the surface; preparing the prepared glassy carbon electrode into a modified electrode through an electrochemical polymerization method; and preparing the molecularly imprinted electrochemical sensor from the prepared modified electrode through an elution method. The sensor prepared from the raw materials and the method has the advantages of simplicity in preparation, good selectivity, good reproducibility, high repeated utilization rate and the like, and realizes sensitive and specific analysis of colchicine in an actual sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical sensors, and in particular relates to a mesoporous polydopamine nanocomposite material, a molecular imprinting electrochemical sensor, and a preparation method and application thereof. Background Art

[0002] Colchicine (Col) is an alkaloid found in plants of the lily family. It has a variety of pharmacological effects, including anti-gout, anti-tumor, and anti-hepatitis, and has special effects on certain cancers and primary gout. Nevertheless, due to the high toxicity of colchicine, even a small amount of colchicine can cause vomiting, diarrhea, renal failure, multiple organ failure, and bone marrow suppression. It has been reported that if the short-term intake of Col exceeds 0.5 mg / kg, the mortality rate will increase significantly. Adults can be poisoned by ingesting 0.11-0.12 mg of Col, and ingesting 20 mg of Col can cause death. At present, a variety of analytical methods for detecting Col have been developed, such as thin layer chromatography-densitometry, high performance liquid chromatography-ultraviolet method, and high performance liquid chromatography-mass spectrometry, but these methods are usually time-consuming, expensive, and cumbersome. Therefore, it is very necessary and urgent to find an efficient and sensitive method for detecting Col.

[0003] Among the related prior arts, the electrochemical method has attracted wide attention due to its advantages of low cost, simple operation, and fast response speed. It is currently one of the most promising and convenient methods for detecting col. According to the survey, col itself is electroactive and is easily oxidized on the electrode surface to lose electrons and generate electrochemical signals. Detection can be achieved by establishing the relationship between different concentrations of col and electrochemical signals. Most of the electrochemical methods currently developed for detecting col use its own electroactive characteristics to develop new nanomaterial-modified electrodes to improve the detection sensitivity of the sensor, but the selectivity in practical applications still needs to be improved. In response to the above problems, molecular imprinted polymers (MIPs) with specific recognition capabilities are used as recognition elements, which can significantly improve the selectivity of the sensor. The currently developed MIP preparation methods (such as precipitation polymerization, bulk polymerization, solid phase synthesis, etc.) are time-consuming, incompletely eluted, unevenly formed on the substrate, and poorly adherent. In addition, multiple reagents (such as template molecules, cross-linking agents, initiators, etc.) are required to participate in the synthesis during preparation, which is easy to cause environmental pollution.

[0004] The electrochemical polymerization method has attracted widespread attention due to its following advantages: (1) the thickness, properties and morphology of the MIP film can be controlled by adjusting the experimental conditions of the electropolymerization (potential, current, charge, solution pH, etc.); (2) the preparation speed is fast and the template is thoroughly eluted; (3) the MIP film prepared by electropolymerization has uniform thickness, strong adhesion to the substrate and good stability; (4) the experiment only requires templates, functional monomers and solvents, and the experimental reagents are few and environmentally friendly. Despite this, the MIP electrochemical sensors currently developed have the problems of obstructed mass transfer, poor electrical signal response and low sensitivity. Therefore, it is urgent to develop a new type of sensor to overcome the above problems. Summary of the invention

[0005] In order to achieve the above-mentioned purpose and solve the above-mentioned problems existing in the prior art, a sensor prepared by the raw material and method of the present invention is prepared by coating a mesoporous polydopamine nanocomposite material loaded with gold nanoparticles on the surface of an electrode and drying the material to obtain a sensitive material layer; a molecular imprinting layer is further formed on the substrate of the sensitive material layer, and the preparation steps of the molecular imprinting layer are as follows: functional monomers are polymerized by electrochemical polymerization to form a polymer layer, wherein the polymer layer contains template molecules; and the template molecules in the polymer layer are removed to form an imprinting cavity in the polymer layer.

[0006] One of the purposes of the present invention is to provide a method for preparing a mesoporous polydopamine nanocomposite material, comprising the following steps: adding mesoporous polydopamine into water and dispersing it uniformly to obtain a suspension; adding an aqueous solution of chloroauric acid trihydrate into the suspension under stirring conditions to react; and separating after the reaction to obtain a mesoporous polydopamine nanocomposite material loaded with gold nanoparticles.

[0007] As a preferred embodiment, the mesoporous polydopamine is prepared by the following method:

[0008] Step S11, dissolving polyoxyethylene polyoxypropylene ether and 1,3,5-mesitylene in an ethanol aqueous solution in a certain proportion, and stirring to obtain a first mixed solution;

[0009] Step S12, adding the tris(hydroxymethyl)aminomethane) aqueous solution to the first mixed solution obtained in step S11 to obtain a second mixed solution;

[0010] Step S13, adding dopamine hydrochloride to the second mixed solution obtained in step S12, and continuing the reaction under stirring;

[0011] Step S14, washing and separating the solution after the reaction in step S13, removing the unreacted template from the separated product, and then vacuum drying to obtain mesoporous polydopamine.

[0012] The second object of the present invention is to provide a mesoporous polydopamine nanocomposite material, which is prepared according to any of the above-mentioned methods for preparing the mesoporous polydopamine nanocomposite material.

[0013] As a preferred solution, the mesoporous polydopamine nanocomposite material has a porous structure with a pore size ranging from 4 to 30 nm.

[0014] The third object of the present invention is to provide a method for preparing a molecular imprinting electrochemical sensor, comprising the following steps:

[0015] Step S21, polishing the surface of the glassy carbon electrode;

[0016] Step S22, taking any one of the above-mentioned mesoporous polydopamine nanocomposite materials and adding it into water to prepare a dispersion, and dropping the obtained dispersion onto the surface of the glassy carbon electrode obtained in step S21 and drying it to obtain a glassy carbon electrode with the mesoporous polydopamine nanocomposite material coated on the surface;

[0017] Step S23, preparing a modified electrode by electrochemical polymerization of the glassy carbon electrode prepared in step S22;

[0018] Step S24, preparing a molecular imprinting electrochemical sensor by eluting the modified electrode prepared in step S23.

[0019] As a preferred embodiment, in step 23, the glassy carbon electrode prepared in step S22 is immersed in an acetate buffer solution containing o-phenylenediamine and col, and a modified electrode is obtained by continuous cyclic voltammetry scanning by electrochemical polymerization, and the molar ratio of col to o-phenylenediamine in the buffer solution is 1:1 to 2.

[0020] As a preferred solution, the modified electrode is obtained by performing 5 to 20 consecutive cyclic voltammetric scans by electrochemical polymerization.

[0021] As a preferred embodiment, the pH value of the acetate buffer solution ranges from 4.0 to 6.0.

[0022] A fourth object of the present invention is to provide a molecular imprinting electrochemical sensor, which is prepared according to any of the above-mentioned methods for preparing a molecular imprinting electrochemical sensor.

[0023] The fifth object of the present invention is to use the molecular imprinting electrochemical sensor described above in the detection of colchicine.

[0024] As a preferred solution, step S31: immersing the prepared molecular imprinting electrochemical sensor in a col standard solution containing different concentrations, wherein one concentration of col solution modifies one sensor, and the concentration and the sensor are in a one-to-one correspondence; taking out after incubation for a period of time, and then rinsing the electrode with ultrapure water to remove unbound col to obtain an incubated electrode, the incubation time is 10 to 15 minutes, recorded as col / MIP / AuNPs@mPDA / GCE, and the concentration of the col standard solution is 2 to 200 μmol / L;

[0025] Step S32: using the col / MIP / AuNPs@mPDA / GCE incubated in step S31 as the working electrode, the Ag / AgCl electrode as the reference electrode, and the platinum wire electrode as the counter electrode, using differential pulse voltammetry to detect and record the electrochemical signals generated by different concentrations of col in the buffer solution, using the concentration of the col standard solution as the abscissa and the generated electrical signal as the ordinate to establish a standard curve;

[0026] Step S33: Obtain the sample solution, place the MIP / AuNPs@mPDA / GCE sensor in the sample solution and incubate for 10 to 15 minutes, rinse the sensor with ultrapure water, and then detect it to obtain the corresponding current signal through electrochemical testing; substitute the generated current signal into the standard curve constructed in step S32 to obtain the concentration of col in the actual sample.

[0027] As a preferred embodiment, in S32 and S33, the electrochemical test is carried out in a 40 mmol / L BR (Brittan-Robinson buffer solution) buffer solution, and the scanning voltage range is 1.1 to 1.5V.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] First, the present invention prepares a gold nanoparticle-loaded mesoporous polydopamine composite material (AuNPs@mPDA) with excellent conductivity, and uses it as a substrate material to improve the signal response of the molecular imprinting sensor; wherein, mPDA is formed by self-assembly of polydopamine molecules, and has a large specific surface area and an ordered mesoporous structure; more importantly, it itself has a strong reducing ability, and can be synthesized in situ by a one-step method. The introduction of AuNPs can greatly accelerate electron transfer, thereby improving the sensitivity of the system.

[0030] Secondly, the present invention also uses a molecular imprinting electrochemical sensor, by using AuNPs@mPDA as a substrate material and o-phenylenediamine (oPD) with high affinity as an electropolymerization functional monomer to construct a molecular imprinting electrochemical sensor based on colchicine (Col), and the present invention couples electrochemical polymerization and imprinting technology to construct a molecular imprinting electrochemical sensor of a high-performance mesoporous polydopamine-based nanocomposite material. The electrochemical sensor prepared by the present invention has the advantages of simple preparation, good selectivity, good reproducibility and high reuse rate, and realizes sensitive and specific analysis of colchicine (Col) in actual samples.

[0031] Third, the molecular imprinting electrochemical sensor based on the AuNPs@mPDA composite material of the present invention is used to detect colchicine (col), and its linear range is as wide as 5 to 200 μmol / L, and the detection limit is as low as 2 μmol / L.

[0032] Fourthly, the present invention adopts electrochemical polymerization to prepare molecularly imprinted polymers with controllable morphology and excellent selectivity. The obtained imprinted cavity specifically binds to colchicine (col) through hydrogen bonding and π-π conjugation, which can improve the selectivity of the sensor.

[0033] Fifth, the molecular imprinting electrochemical sensor constructed by the present invention can realize the reusability of the sensor through electrochemical reduction and recombination, and can still maintain 92.7% of the initial value after 10 consecutive detections. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the preparation process of the AuNPs@mPDA composite material of the present invention;

[0035] Figure 2 This is a specific construction flow chart of the sensor in the present invention;

[0036] Figure 3 is a transmission electron microscope (TEM) image of the AuNPs@mPDA composite material of the present invention;

[0037] Figure 4 The X-ray photoelectron spectrum (XPS) diagram of the AuNPs@mPDA composite material of the present invention: the abscissa is the binding energy);

[0038] Figure 5 The influence of different ratios of template molecules to functional monomers on the current signal in the present invention: the abscissa is the ratio of template molecules to functional monomers, and the ordinate is the current signal;

[0039] Figure 6 The effect of the number of electrochemical polymerization cycles on the current signal in the present invention: the horizontal axis is the number of electrochemical polymerization cycles, and the vertical axis is the current signal;

[0040] Figure 7 The effect of the pH value of the electrochemical polymerization buffer solution on the current signal in the present invention: the abscissa is the pH value of the electrochemical polymerization buffer solution, and the ordinate is the current signal;

[0041] Figure 8 It is a current signal diagram corresponding to different concentrations of the col standard solution in the present invention: the abscissa (X-axis) is the potential, the ordinate (Y-axis) is the current signal, and the Z-axis is the col standard solution of different concentrations;

[0042] Fig. 9 It is a linear relationship diagram between different concentrations of the col standard solution and the current signal in the present invention: the abscissa is the col concentration, and the ordinate is the current signal;

[0043] Fig.10 The reproducibility diagram of the molecular imprinting electrochemical sensor constructed in the present invention between batches and within batches: the abscissa (X-axis) is 6 parallel sensors, the ordinate (Y-axis) is the current signal, and the Z-axis is the test within and between batches;

[0044] Fig.11 This is a diagram of the reusability of the molecular imprinted electrochemical sensor of the present invention: the horizontal axis is the number of reusable times, and the vertical axis is the current signal; DETAILED DESCRIPTION

[0045] In order to make the technical means, creative features, objectives and beneficial effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0046] In addition, in order to better illustrate the present invention, numerous specific details are given in the specific embodiments below. Those skilled in the art should understand that the present invention can also be implemented without certain specific details. In other embodiments, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present invention.

[0047] The invention provides a highly conductive mesoporous polydopamine nanocomposite material and a preparation method thereof. The composite material comprises mPDA and AuNPs loaded on the surface of the mPDA through the self-reduction property of the mPDA itself.

[0048] In order to achieve the above technical objectives, the present invention comprises the following steps:

[0049] S11. Preparation of mPDA:

[0050] The template molecules polyoxyethylene polyoxypropylene ether (F127) and 1,3,5-trimethylbenzene (TMB) were dissolved in an ethanol-water solution. After stirring for a period of time, a tris (hydroxymethyl)aminomethane (Tris) aqueous solution was added to the mixed solution. Subsequently, dopamine hydrochloride was added and the reaction continued under stirring. Finally, the obtained solution was washed and centrifuged with ethanol, acetone, and ethanol in turn. The washed product still needed to be added to an ethanol-acetone mixed solution (V 乙醇 :V 丙酮 =2:1) ​​was subjected to ultrasonic treatment to remove the unreacted template. The final product was vacuum dried to obtain mPDA solid for further use.

[0051] Preferably, in step S11, the dosage ratio of polyoxyethylene polyoxypropylene ether (F127) and 1,3,5-trimethylbenzene (TMB) is 1:1, the dosage of ethanol aqueous solution is 60 mL (ethanol): 65 mL (water), wherein the mass of F127 is 0.36 g, the mass of TMB is 0.36 g, and the stirring time of the two is 30 min; the concentration of Tris is 9 mg / mL, and the dosage is 10 mL; the amount of dopamine hydrochloride added is 60 mg, and the stirring time is 24 h; the centrifugal speed is 10000 rpm, the centrifugal time is 30 min / time, and the number of centrifugations is 3 times; the ultrasonic power is 99%, the ultrasonic time is 30 min / time, and the number of ultrasonic times is 3 times; the vacuum drying temperature is 40°C.

[0052] S12. Preparation of AuNPs@mPDA:

[0053] The mPDA solid prepared in step S11 is added to water and dispersed by ultrasound to obtain a dispersion. Then, under stirring conditions, an aqueous solution of chloroauric acid trihydrate (HAuCl4·3H2O) is added to the above solution, and after a period of reaction using the self-reduction property of mPDA itself without adding an additional reducing agent, a precipitate is obtained by centrifugation, and then washed three times with ethanol to remove residual substances, and finally vacuum dried to obtain the AuNPs@mPDA composite material;

[0054] Preferably, in step S12, the concentration of mPDA in the dispersion is 2 mg / mL, and the dosage is 4-8 mL; the concentration of HAuCl4·3H2O is 10 mg / mL, and the dosage is 50-200 μL, and the stirring time is 1 h; the centrifugal speed is 12000 rpm, the centrifugal time is 20 min / time, and the number of centrifugation is 3 times; the vacuum drying temperature is 60°C.

[0055] Secondly, the present invention also provides a method for preparing a molecular imprinting electrochemical sensor, including modifying a substrate material, that is, coating the AuNPs@mPDA composite material on an electrode surface and drying it to obtain a sensitive material layer; further designing a molecular imprinting layer on the substrate of the sensitive material layer, polymerizing functional monomers by electrochemical polymerization to form a polymer layer, wherein the polymer layer contains template molecules; removing the template molecules in the polymer layer, so that the polymer layer forms an imprinting cavity. The construction process of the molecular imprinting electrochemical sensor includes the following steps:

[0056] S21, treating a glassy carbon electrode (GCE) with aluminum oxide powders of different particle sizes in sequence, then ultrasonically cleaning in water, ethanol, acetone and water in sequence and drying, to obtain a treated glassy carbon electrode;

[0057] Preferably, in step S21, the diameter of the glassy carbon electrode is 3 mm; the particle sizes of the aluminum oxide powder used are 0.3 μm and 0.05 μm, respectively. The glassy carbon electrode (GCE, 3 mm) is treated with 0.3 μm and 0.05 μm aluminum oxide powders, respectively, and then ultrasonically cleaned in water, ethanol, acetone and water, respectively, and dried, to obtain a treated glassy carbon electrode.

[0058] S22, ultrasonically dispersing the AuNPs@mPDA composite material prepared in step 12 in ultrapure water, and dropping the prepared AuNPs@mPDA dispersion onto the surface of the glassy carbon electrode treated in step S21, and drying to obtain AuNPs@mPDA / GCE;

[0059] Preferably, in step 22, the concentration of the AuNPs@mPDA dispersion is 1 mg / mL; the amount used during dropwise addition is 6 μL; the drying temperature is 37°C and the time is 1 hour. The AuNPs@mPDA composite material prepared in step S12 is ultrasonically dispersed in ultrapure water to prepare a 1 mg / mL AuNPs@mPDA dispersion; 6 μL of the AuNPs@mPDA dispersion is pipetted with a pipette and dropped onto the surface of the glassy carbon electrode treated in step S21, and AuNPs@mPDA / GCE is obtained after drying for 1 hour.

[0060] S23, immersing the AuNPs@mPDA / GCE obtained in step 22 in an acetate buffer solution containing o-phenylenediamine (oPD, as a functional monomer) and colchicine (col, as a template molecule), and performing a cyclic voltammetry scan within a fixed voltage range; after the scan, taking out the electrode, and drying it at room temperature to obtain an electrode denoted as oPD / AuNPs@mPDA / GCE;

[0061] Preferably, the amount ratio (molar ratio) of col (template molecule) to oPD (functional monomer) is 1:1-2, the concentration of acetate buffer solution (sodium acetate-acetic acid buffer solution) is 0.1 mol / L, and the pH value is 4.0-6.0; the potential range of cyclic voltammetry scanning is -0.2-1.0 V, the scanning speed is 50 mV / s, and the number of cycles is 5-20 times. The AuNPs@mPDA / GCE obtained in step S22 is immersed in 4 mL of sodium acetate-acetic acid buffer solution (0.1 M, pH 4.0-6.0) containing o-phenylenediamine (oPD, as a functional monomer) and colchicine (col, as a template molecule), wherein the amount ratio (molar ratio) of col to oPD is 1:1-2 (that is, in the sodium acetate-acetic acid buffer solution, the colchicine content is 4 mM and the o-phenylenediamine content is 4-8 mM). Then, through electrochemical polymerization, 5 to 20 continuous cyclic voltammetry scans were performed at 50 mV / s in the voltage range of -0.2 to 1.0 V. After the scan, the electrode was taken out and dried at room temperature to obtain a modified electrode recorded as oPD / AuNPs@mPDA / GCE.

[0062] S24. Soak the modified electrode oPD / AuNPs@mPDA / GCE obtained in step S23 in an elution solution for a period of time, then rinse with ultrapure water and dry to obtain a mesoporous polydopamine nanocomposite-based molecular imprinting electrochemical sensor loaded with gold nanoparticles, recorded as MIP / AuNPs@mPDA / GCE.

[0063] Preferably, the elution solution is a mixed solution of ethanol and acetic acid in a ratio of V 乙醇 :V 乙酸 =9:1, the soaking time is 3 min. The modified electrode oPD / AuNPs@mPDA / GCE obtained in step S23 is soaked in an elution solution of ethanol and acetic acid (V 乙醇 :V 乙酸 =9:1) for 3 min, then rinsed with ultrapure water and dried to obtain a mesoporous polydopamine nanocomposite-based molecular imprinting electrochemical sensor loaded with gold nanoparticles, denoted as MIP / AuNPs@mPDA / GCE.

[0064] The present invention also relates to a use of a molecular imprinting electrochemical sensor based on AuNPs@mPDA for detecting colchicine, the steps of which are as follows:

[0065] S31, immersing the electrochemical sensor prepared in the above step S24 into a standard solution containing colchicine (Col) of different concentrations, wherein one concentration of the Col solution modifies one sensor, and the concentration and the sensor are in a one-to-one correspondence; after incubation for a period of time, taking out the electrode, and then rinsing the electrode with ultrapure water to remove unbound Col, obtaining an incubated electrode, recorded as Col / MIP / AuNPs@mPDA / GCE;

[0066] S32, using the col / MIP / AuNPs@mPDA / GCE incubated in step S31 as the working electrode, the Ag / AgCl (saturated KCl) electrode as the reference electrode, and the platinum wire electrode as the counter electrode, using a CHI660E electrochemical workstation to detect and record the electrochemical signals generated by different concentrations of col in a buffer solution using differential pulse voltammetry (DPV), using the concentration of the col standard solution as the abscissa and the generated electrical signal as the ordinate to establish a standard curve;

[0067] S33. Detection of actual sample col: first obtain the sample solution, place the MIP / AuNPs@mPDA / GCE sensor in the sample solution and incubate for a period of time, then rinse the sensor with ultrapure water, and then detect it, and obtain the corresponding current signal through the DPV method; substitute the generated current signal into the standard curve constructed in step S32 to obtain the concentration of col in the actual sample, thereby realizing the detection of colchicine (col) in unknown samples.

[0068] Preferably, the concentration of the col standard solution in step S31 is 2 to 200 μmol / L.

[0069] Preferably, the incubation time in step S31 and step S33 is 10 to 15 minutes.

[0070] Preferably, the electrochemical test (DPV) in step S32 and step S33 is performed in a 40 mmol / L BR (pH=2.0) buffer solution, with a scanning voltage range of 1.1 to 1.5 V, an amplitude of 0.05 V, a pulse width of 0.05 s, and a pulse period of 0.5 s.

[0071] Example 1

[0072] This embodiment provides a method for preparing an AuNPs@mPDA composite material, comprising the following steps:

[0073] S11, 0.36g of polyoxyethylene polyoxypropylene ether (F127) and 0.36g of 1,3,5-mesitylene (TMB) were dissolved in 125mL of ethanol aqueous solution (V 乙醇 :V 水=48:52), stirred for 30 min, and then 10 mL of 9 mg / mL tris(hydroxymethyl)aminomethane (Tris) aqueous solution was added to the mixed solution. Subsequently, 60 mg of dopamine hydrochloride was added and stirred at room temperature for 24 h. The obtained solution was washed with ethanol, acetone, and ethanol for 3 times, each time for 3 min, and the centrifugal speed was 10000 rpm; the washed product still needed to be added with ethanol-acetone mixed solution (V 乙醇 :V 丙酮 =2:1) ​​was subjected to ultrasonic treatment for 3 times to remove the unreacted template, each ultrasonic treatment lasted for 30 min, and the ultrasonic power was 99%; finally, the obtained product was vacuum dried at 40° C. for further use.

[0074] S12. Take 5 mL of 2 mg / mL mPDA suspension and ultrasonically disperse it (mPDA solid is added to water and a suspension is obtained by ultrasonic dispersion), then take 100 μL of 10 mg / mL HAuCl4·3H2O solution and add it to the above mPDA suspension. Without adding any additional reducing agent, stir the reaction for 1 hour using the self-reduction property of mPDA itself. Subsequently, centrifuge the resulting solution to obtain a precipitate, wash it with ethanol three times, 20 minutes each time, at a centrifugal speed of 12000 rpm, and finally vacuum dry it to obtain the AuNPs@mPDA composite material.

[0075] Figure 3 : The TEM image of the AuNPs@mPDA composite material obtained in Example 1 is a spherical shape with a rough and uneven surface, an average particle size of 150 nm, a porous structure, a pore size of 4 to 30 nm, and a relatively wide pore size distribution, which is conducive to electron transmission. The in-situ loaded AuNPs are uniformly dispersed on the mPDA, and the AuNPs particle size is about 4 nm.

[0076] Figure 4 This is the XPS graph of the AuNPs@mPDA composite material obtained in Example 1. The results show the presence of C, N, O and Au elements in the composite material.

[0077] Example 2

[0078] This embodiment provides a method for preparing a molecular imprinting electrochemical sensor, comprising the following steps:

[0079] S21. Treat the glassy carbon electrode (GCE, 3 mm) with 0.3 μm and 0.05 μm aluminum oxide powders in turn, then ultrasonically clean and dry them in water, ethanol, acetone and water in turn to obtain a treated glassy carbon electrode.

[0080] S22. Ultrasonic disperse the AuNPs@mPDA composite material prepared in step S12 of Example 1 in ultrapure water to prepare 1 mg / mL AuNPs@mPDA dispersion; use a pipette to draw 6 μL of AuNPs@mPDA dispersion and drop it onto the surface of the glassy carbon electrode treated in step S21, and obtain AuNPs@mPDA / GCE after drying for 1 hour.

[0081] S23, immerse the AuNPs@mPDA / GCE obtained in step S22 in 4mL sodium acetate-acetic acid buffer solution (0.1M, pH=5.0) containing o-phenylenediamine (oPD, as a functional monomer) and colchicine (col, as a template molecule), wherein the amount ratio of col (template molecule) to oPD (functional monomer) is 1:1.5 (in the sodium acetate-acetic acid buffer solution, the colchicine content is 4mM and the o-phenylenediamine content is 6mM). Then, by electrochemical polymerization (CV method), 10 continuous cyclic voltammetry scans are performed at 50mV / s in the voltage range of -0.2 to 1.0V. After the scan, the electrode is taken out and dried at room temperature to obtain a modified electrode recorded as oPD / AuNPs@mPDA / GCE.

[0082] S24, immersing the modified electrode oPD / AuNPs@mPDA / GCE obtained in step S23 in an elution solution of ethanol and acetic acid (V 乙醇 :V 乙酸 =9:1) for 3 min, then rinsed with ultrapure water and dried to obtain a mesoporous polydopamine nanocomposite-based molecular imprinting electrochemical sensor loaded with gold nanoparticles, denoted as MIP / AuNPs@mPDA / GCE.

[0083] Embodiment 3-6

[0084] The other conditions are the same as those in Example 2, except that the ratio of col (template molecule) to oPD (functional monomer) in step S23 is as follows:

[0085] The AuNPs@mPDA / GCE obtained in step S22 was immersed in a 0.1 mol / L sodium acetate-acetic acid buffer solution (pH=5.0) containing o-phenylenediamine (oPD, as a functional monomer) and colchicine (col, as a template molecule), wherein the contents of col (template molecule) and oPD (functional monomer) were 4mM:4mM, 4mM:5mM, 4mM:7mM, 4mM:8mM, respectively, that is, the amount ratio (molar ratio) of the two was 1:1, 1:1.25, 1:1.75, 1:2, respectively, and then, by electrochemical polymerization, 10 continuous cyclic voltammetry scans were performed at 50mV / s in the voltage range of -0.2 to 1.0V. After the scan, the electrode was taken out and dried at room temperature to obtain a modified electrode recorded as oPD / AuNPs@mPDA / GCE.

[0086] Figure 5 In Example 2-6, when the molar ratio of col (template molecule) to oPD (functional monomer) in Example 2 is 1:1.5, the molecular imprinting electrochemical sensor can obtain the best response signal. If the functional monomer oPD is too much, the formed cavity sites will be insufficient, resulting in reduced signal; similarly, when the number of template molecules col is too much, the recognition efficiency of the imprinting cavity will be reduced, hindering signal transmission.

[0087] Embodiment 7-9

[0088] The other conditions are the same as those in Example 2, except that the pH of the buffer solution in step S23 is different, as follows:

[0089] The AuNPs@mPDA / GCE obtained in step S22 was immersed in 4 mL of sodium acetate-acetic acid buffer solution (0.1 M, pH = 5.0) containing o-phenylenediamine (oPD, as a functional monomer) and colchicine (col, as a template molecule), wherein the amount ratio of col (template molecule) to oPD (functional monomer) was 1:1.5 (in the sodium acetate-acetic acid buffer solution, the colchicine content was 4 mM and the o-phenylenediamine content was 6 mM). Then, by electrochemical polymerization, continuous cyclic voltammetry scans were performed at 50 mV / s in the voltage range of -0.2 to 1.0 V for 5, 15, and 20 times, respectively. After the scan, the electrode was taken out and dried at room temperature to obtain a modified electrode recorded as oPD / AuNPs@mPDA / GCE.

[0090] Figure 6 It is shown in Examples 2, 7, 8 and 9 that if the number of polymerization cycles is too small, the molecular imprinted film layer formed will be too thin, which will reduce the imprinting sites; while if the number of polymerization cycles is too large, the film layer will be too thick, which will hinder electron transfer. Therefore, the maximum response signal can only be obtained when the number of continuous cyclic voltammetry scans is 10 times.

[0091] Examples 10-13

[0092] The other conditions are the same as those in Example 2, except that the number of continuous cyclic voltammetry scans in step S23 is different, as follows:

[0093] The AuNPs@mPDA / GCE obtained in step S22 was immersed in 4 mL of sodium acetate-acetic acid buffer solution (0.1 M, pH = 4.0-6.0) containing o-phenylenediamine (oPD, as a functional monomer) and colchicine (col, as a template molecule), wherein the amount ratio of col (template molecule) to oPD (functional monomer) was 1:1.5 (in the sodium acetate-acetic acid buffer solution, the colchicine content was 4 mM and the o-phenylenediamine content was 6 mM), and the pH values ​​of the sodium acetate-acetic acid buffer solution were sequentially used at 4.0, 4.5, 5.5, and 6.0 for the experiment, and then, by electrochemical polymerization, 10 continuous cyclic voltammetry scans were performed at 50 mV / s in the voltage range of -0.2 to 1.0 V. After the scan, the electrode was taken out and dried at room temperature to obtain a modified electrode recorded as oPD / AuNPs@mPDA / GCE.

[0094] Figure 7 In Examples 2, 10, 11, 12, and 13, when the pH value of the acetate buffer solution in Example 2 is 5.0, the current response of the molecular imprinting sensor is the largest, indicating that the interaction between the o-phenylenediamine free radical and colchicine is the strongest.

[0095] Comparative Example 1

[0096] The other conditions are the same as those of Example 2, and the only difference of Comparative Example 1 is that no template molecule colchicine (col) is added during the polymerization process of step S23, and the obtained sensor is recorded as NIP / AuNPs@mPDA / GCE. The details are as follows:

[0097] The sensor MIP / AuNPs@mPDA / GCE provided in Example 2 and the NIP / AuNPs@mPDA / GCE in Comparative Example 1 were immersed in an aqueous solution containing 5 mmol / L potassium ferrocyanide and 0.1 mol / L potassium chloride, and the electrochemical properties of the sensor were investigated by cyclic voltammetry and electrochemical impedance spectroscopy, respectively. The scanning range of the cyclic voltammetry (CV) was set to -0.2 V to 0.6 V, and the scanning rate was 100 mV s -1 The frequency range of electrochemical impedance spectroscopy (EIS) was set to 0.1 Hz to 0.1 MHz, the amplitude was 10 mV, and the open circuit voltage was 0.27 V.

[0098] Due to the lack of effective imprinting sites, NIP / AuNPs@mPDA / GCE showed lower oxidation peak current and larger impedance value than that of GCE.

[0099] Application Examples

[0100] The MIP / AuNPs@mPDA / GCE with the best performance provided in Example 2 was immersed in a colchicine standard solution containing different concentrations, incubated for 10 to 15 minutes and then taken out (preferably 15 minutes here), and then the electrode was rinsed with ultrapure water to remove unbound col, and the incubated electrode was obtained, recorded as col / MIP / AuNPs@mPDA / GCE; the col standard solutions were 2, 5, 8, 10, 25, 50, 80, 100, 150, and 200 μM, respectively.

[0101] The above product (col / MIP / AuNPs@mPDA / GCE) was used as the working electrode, the Ag / AgCl (saturated KCl) electrode was used as the reference electrode, and the platinum wire electrode was used as the counter electrode. The electrochemical signal generated by the product was detected and recorded in a 40mmol / L BR (pH=2.0) buffer solution using differential pulse voltammetry (DPV) using a CHI660E electrochemical workstation. The scanning range of DPV was 1.1-1.5V, the amplitude was 0.05V, the pulse width was 0.05s, the pulse period was 0.5s, and the sampling width was 0.0167s. The current signal of col was used as the ordinate and the concentration of the corresponding col standard solution was used as the abscissa to establish the corresponding standard curve for the detection of col concentration in actual samples.

[0102] from Figure 8 , 9 It can be seen that as the concentration of col increases, the peak current signal gradually increases, and a good linear relationship is shown in the concentration range of 5 to 200 μM. The standard curve is I col =3.74C col +45.07(R 2 =0.999), and the detection limit was 2 μM.

[0103] Analytical performance of molecularly imprinted electrochemical sensors

[0104] The best performing MIP / AuNPs@mPDA / GCE provided in Example 2 was immersed in a standard solution containing 50 μM colchicine (col), incubated for 15 min, and then taken out, and then the electrode was rinsed with ultrapure water to remove unbound col, and the incubated electrode was obtained, which was recorded as col / MIP / AuNPs@mPDA / GCE. The reproducibility and reusability of the molecular imprinting sensor were investigated.

[0105] from Fig.10As can be seen from the results, the reproducibility RSDs of the sensors within and between batches were 4.6% and 3.0%, respectively, indicating that the developed product has excellent reproducibility; in addition, the same molecular imprinting electrochemical sensor was subjected to 10 consecutive cycles of the col test and elution steps (see Fig.11 ), it was found that after 10 consecutive detections of the sensing response of col, the peak current after the 10th regeneration was only slightly lower than the initial response by 7.3% due to the slight degradation of the imprinted holes, showing good reusability.

[0106] Effect Example

[0107] The actual samples were analyzed using the constructed mesoporous polydopamine nanocomposite material-based molecular imprinting electrochemical sensor loaded with gold nanoparticles, and the steps are as follows:

[0108] (1) Buy edible lilies, weigh 2 g of edible lilies, crush them, add 6 mL of ethanol for extraction, shake for 20 min, centrifuge at 1000 rpm for 10 min, and extract the supernatant. Further, filter with a 0.22 μm filter membrane to obtain the final extract. The molecular imprinting electrochemical sensor analysis method constructed above was used for testing.

[0109] (2) The extracts containing 10 and 20 μM col were prepared by the standard addition method and tested using the analytical method constructed above to verify that the constructed method has good practicality.

[0110] As shown in Table 1, no COL was detected in the blank sample without spike addition. After spike addition, the recovery rate of the molecular imprinting electrochemical sensor we constructed was between 98.3% and 102.5%, indicating that the method of the present invention is reliable and practical; and the purpose of detecting COL in unknown samples is achieved.

[0111] Table 1 Detection of the content of col in edible lily using the constructed molecular imprinting electrochemical sensing method (n=3).

[0112]

[0113] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a mesoporous polydopamine nanocomposite material, characterized in that: The method comprises the following steps: adding mesoporous polydopamine into water and dispersing it uniformly to obtain a suspension; adding trihydrate chloroauric acid aqueous solution into the suspension under stirring conditions to react; and separating after the reaction to obtain a mesoporous polydopamine nanocomposite material loaded with gold nanoparticles.

2. The method for preparing a mesoporous polydopamine nanocomposite material according to claim 1, characterized in that: The mesoporous polydopamine is prepared by the following method: Step S11, dissolving polyoxyethylene polyoxypropylene ether and 1,3,5-mesitylene in an ethanol aqueous solution in a certain proportion, and stirring to obtain a first mixed solution; Step S12, adding the tris(hydroxymethyl)aminomethane) aqueous solution to the first mixed solution obtained in step S11 to obtain a second mixed solution; Step S13, adding dopamine hydrochloride to the second mixed solution obtained in step S12, and continuing the reaction under stirring; Step S14, washing and separating the solution after the reaction in step S13, removing the unreacted template from the separated product, and then vacuum drying to obtain mesoporous polydopamine.

3. A mesoporous polydopamine nanocomposite material, characterized in that: The mesoporous polydopamine nanocomposite material is prepared according to the method for preparing the mesoporous polydopamine nanocomposite material according to claim 1 or 2.

4. The mesoporous polydopamine nanocomposite material according to claim 3, characterized in that: The mesoporous polydopamine nanocomposite material has a porous structure with a pore size ranging from 4 to 30 nm.

5. A method for preparing a molecular imprinting electrochemical sensor, characterized in that: The steps include: Step S21, polishing the surface of the glassy carbon electrode; Step S22, adding the mesoporous polydopamine nanocomposite material according to claim 3 or 4 into water to prepare a dispersion, dripping the obtained dispersion onto the surface of the glassy carbon electrode obtained in step S21 and drying it to obtain a glassy carbon electrode with the mesoporous polydopamine nanocomposite material coated on the surface; Step S23, preparing a modified electrode by electrochemical polymerization of the glassy carbon electrode prepared in step S22; Step S24, preparing a molecular imprinting electrochemical sensor by eluting the modified electrode prepared in step S23.

6. The method for preparing a molecularly imprinted electrochemical sensor according to claim 5, characterized in that: In the step 23, the glassy carbon electrode prepared in step S22 is immersed in an acetate buffer solution containing o-phenylenediamine and col, and a modified electrode is obtained by continuous cyclic voltammetry scanning by electrochemical polymerization. The molar ratio of col to o-phenylenediamine in the acetate buffer solution is 1:1-2.

7. The method for preparing a molecularly imprinted electrochemical sensor according to claim 6, characterized in that: The modified electrode was obtained by electrochemical polymerization method and 5 to 20 consecutive cyclic voltammetry scans.

8. The method for preparing a molecularly imprinted electrochemical sensor according to claim 6 or 7, characterized in that: The pH value of the acetate buffer solution ranges from 4.0 to 6.

0.

9. A molecular imprinting electrochemical sensor, characterized in that: The method for preparing a molecular imprinting electrochemical sensor according to any one of claims 5 to 8.

10. Use of the molecular imprinting electrochemical sensor according to claim 9 in the detection of colchicine.

11. The use of the molecular imprinting electrochemical sensor in the detection of colchicine according to claim 10, characterized in that: The steps include: Step S31: immersing the prepared molecular imprinting electrochemical sensor in a standard solution containing different concentrations of col, wherein one concentration of col solution modifies one sensor, and the concentration and the sensor are in a one-to-one correspondence; after incubation for a period of time, taking out the electrode, and then rinsing the electrode with ultrapure water to remove unbound col, to obtain an incubated electrode, the incubation time is 10-15 min, recorded as col / MIP / AuNPs@mPDA / GCE, and the concentration of the col standard solution is 2-200 μmol / L; Step S32: using the col / MIP / AuNPs@mPDA / GCE incubated in step S31 as the working electrode, the Ag / AgCl electrode as the reference electrode, and the platinum wire electrode as the counter electrode, using differential pulse voltammetry to detect and record the electrochemical signals generated by different concentrations of col in the buffer solution, using the concentration of the col standard solution as the abscissa and the generated electrical signal as the ordinate to establish a standard curve; Step S33: Obtain the sample solution, place the MIP / AuNPs@mPDA / GCE sensor in the sample solution and incubate for 10-15 min, then rinse the sensor with ultrapure water and perform detection to obtain the corresponding current signal through electrochemical testing; substitute the generated current signal into the standard curve constructed in step S32 to obtain the concentration of col in the actual sample.

12. Use of the molecular imprinting electrochemical sensor according to claim 11 in the detection of colchicine, characterized in that: In S32 and S33, the electrochemical test is performed in a BR buffer solution.